Bushido’s Role in the Growth of Pre-World War II Japanese Nationalism - Patterson, William R. (Revista de Artes Marciales Asiáticas, 2012)
Though some attention has been given to the role that Bushido (the ethical system of the samurai) may have played in the development of nationalism in post-Meiji Japan, the martial arts themselves have largely been absolved of any complicity. I argue in this article that the martial arts did in fact play a role in the rise of Japanese nationalism and therefore share some of the blame for the events that took place leading up to and during the Second World War. The article demonstrates how the martial arts were used to popularize the precepts of Bushido and how these precepts in turn lead to the growth of expansionist nationalism. It also shows how the martial arts were used in the educational system and the military to inculcate the Bushido notions of honor and loyalty in the general public.